Using preoperative ultrasound vascularity characteristics to estimate medullary thyroid cancer - Luying Gao; Liyuan Ma; Xiaoyi Li; Chunhao Liu; Naishi Li; Xiaolan Lian; Weibo Xia; Ruifeng Liu; Xinlong Shi; Jiang Ji; Aonan Pan; Yu Xia; et al. (Cancer Imaging, 2023)
Abstract Background The early diagnosis of medullary thyroid carcinoma (MTC) is still a challenge in clinical practice. Based on ultrasound features, many MTC cases without suspicious characteristics are not categorized as high risk for malignancy. This study was designed to comprehensively investigate the ultrasonic features of MTC on ultrasound and help identify thyroid nodules with a high risk of MTC. Methods Between 2017 and 2023, we retrospectively reviewed 116 consecutive thyroid nodules with a histologic diagnosis of MTC who had undergone preoperative ultrasound examination. According to the ultrasonic criteria for risk classification, nodules were classified as “ultrasound-high suspicious” (h-MTC) and “ultrasound-low suspicious” (l-MTC). Using the same database, a tumour size- and risk evaluation-matched control group comprising 62 lesions was randomly selected to compare the vascularity features of l-MTC disease. Results We identified 85 h-MTC nodules (73.3%) and 31 l-MTC nodules (26.7%). For patients with l-MTC disease, 22/31 (71.0%) of the lesions were followed up for a period before fine needle aspiration (FNA) or surgery. We observed more penetrating branching vascularity in the l-MTC group than in the benign nodule group (23/31, 74.2% vs. 5/59, 4.8%, P < 0.001). We also showed that more CHAMMAS IV patterns (central blood flow greater than perinodular flow) (87.1% vs. 32.3%, P < 0.001)) and CHEN IV patterns (penetrating vascularity) (100% vs. 25.8%, P < 0.001) were found in l-MTC than benign nodules. Conclusions Vascularity features can help differentiate l-MTC from benign nodules; moreover, we report a novel sonographic vascularity pattern of l-MTC disease, penetrating branching vascularity. The utilization of vascularity features will help to identify MTC among nodules with low-intermediate suspicion by ultrasound risk classification to ensure appropriate clinical management.